Breathing through a spirometer perturbs balance - Clavel, L.; Attali, V.; Jacq, O.; Nierat, M.; Similowski, T.; Rouch, P.; Sandoz, B. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Natural breathing is known to induce at each inspiration/expiration, minimal perturbations of body balance that are compensated by movement of trunk and lower limb (Hodges et al. 2002). This phenomenon called posturo ventilatory synchronization may be impaired (Manor et al. 2012). Its evaluation requires simultaneous assessments of ventilation profile and postural control, using the less disruptive methods. Spirometry is the reference method to assess the ventilatory parameters. It requires however to connect the subject to the spirometer, using a mouthpiece, that is known to modify significantly the respiratory frequency (Gilbert et al. 1972) and may influence the postural control. The Optoelectronic Plethysmography (OEP) was validated as an alternative non-disruptive method to assess ventilation as it allows subjects to breathe naturally. Evidently, non-contact measure of ventilation by camera is supposed to induce no perturbation of postural control, and may be more appropriate than spirometer to assess the posturo ventilator synchronization. The objective of this study was to evaluate the postural perturbations due to the use of the spirometer, by comparing it to the OEP method, on postural control.